1995
DOI: 10.1038/bjc.1995.516
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and preclinical evaluation of humanised A33 immunoconjugates for radioimmunotherapy

Abstract: Summary A humanised IgGl/k version of A33 (hA33) has been constructed and expressed with yields up to 700 mg 1' in mouse myeloma NS0 cells in suspension culture. The equilibrium dissociation constant of hA33 (KD= 1.3 al., 1990, 1994). A phase I/II study has been conducted (Welt et al., 1994) with this murine antibody, in which some tumour responses were observed at the maximum tolerated dose (75 mCi m-2). The major limiting toxicity was haematological, as observed in almost all therapy studies with radioim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 23 publications
1
67
0
Order By: Relevance
“…It is also expressed on normal colonic epithelial cells but no other normal tissues (6). The humanized IgG1 antibody huA33 has high affinity for its target antigen (9), is internalized on binding, and is safe and tolerable when given to patients alone (10,11), in combination with chemotherapy (12), and when radiolabeled (13). 131 I-huA33 can cause targeted delivery of radiation to colon cancer cells and is retained in the tumor for 6 wk (13).…”
mentioning
confidence: 99%
“…It is also expressed on normal colonic epithelial cells but no other normal tissues (6). The humanized IgG1 antibody huA33 has high affinity for its target antigen (9), is internalized on binding, and is safe and tolerable when given to patients alone (10,11), in combination with chemotherapy (12), and when radiolabeled (13). 131 I-huA33 can cause targeted delivery of radiation to colon cancer cells and is retained in the tumor for 6 wk (13).…”
mentioning
confidence: 99%
“…In view of the long retention time of mAb A33 in tumors, high tumor uptake, and minimal gut toxicity observed in these trials, a humanized version of mAb A33 was constructed to enable repeated dosing without immunogenicity (21). Two phase I trials with huA33 have been conducted, with huA33 alone and huA33 with chemotherapy in patients with colorectal carcinoma (22,23).…”
mentioning
confidence: 99%
“…We have been evaluating alternative reagents comprising multivalent Fab's produced by chemical cross-linking. Chemically cross-linked di-Fab (DFM) and tri-Fab (TFM) have been prepared from the mouse-human chimeric Fab' fragment of B72.3 (King et al, 1994) and an engineered human form of the antibody (King et al, 1995). Biodistribution studies with these antibodies have revealed higher tumour accumulation than seen with scFvs, although clearance from the blood is still rapid.…”
mentioning
confidence: 99%